TV SERIES AS A MODERN DIDACTIC TOOL FOR FOREIGN LANGUAGE TEACHING - Rybalka, Nataliia; Herasymenko , Olha (Studies in Comparative Education, 2022)
A foreign language is an obligatory subject of the curriculum of every educational institution. Undoubtedly, this subject requires the use of special methods and lecturer’s teaching skill. The main difficulty while studying a foreign language is mastering the language outside the environment of its use, i.e., the lack of the opportunity to communicate with native speakers. Therefore, one of the most important tasks assigned to the lecturer is the creation of real and imaginary situations of communication in a foreign language lesson using various methods of work. To achieve this goal, the lecturer can use videos and all kinds of video materials, which are of great importance in learning a foreign language. This explains the popularity of films, TV series and video films both outside the educational process and for the development of all the skills acquired in the process of studying a foreign language. In addition, the use of video films in the educational process increases the motivation to learn foreign languages. Motivation as a system of internal stimuli, impulses, emotions and desires is one of the main psychological factors in mastering foreign languages. As the title implies, the present article deals with issues related to the choice of TV series as one of the modern didactic tools used while teaching foreign languages. Particular attention is given to the advantages and disadvantages of using the series in the educational process. As the title implies, the article describes arguments that are given in favor of this teaching method in comparison with educational, short and full-length films. The article distinguishes and describes the types and formats of serials, the criteria for their selection in order to use them while teaching, as well as the stages of working with each series. Authors of this paper propose a list of recommended series for learning English and German languages.